Respuesta :
Answer:
x = 3, y = 3
Step-by-step explanation:
Given the 2 equations
3x + 3y = 18 → (1)
x + 2y = 9 → (2)
Multiplying (2) by - 3 and adding the result to (1) will eliminate the x- term
- 3x - 6y = - 27 → (3)
Add (1) and (3) term by term to eliminate x
0 - 3y = - 9
- 3y = - 9 ( divide both sides by - 3 )
y = 3
Substitute y = 3 into either of the 2 equations and solve for x
Substituting into (2)
x + 2(3) = 9
x + 6 = 9 ( subtract 6 from both sides )
x = 3
solution is x = 3, y = 3
Answer:
x = 3 , y = 3
Step-by-step explanation:
- 3x + 3y = 18 -- (1)
- x + 2y = 9 --(2)
Dividing (1) by 3 : x + y = 6 --(3)
x = 6 - y --(3)'
Substituting (3)' into (2),
(6 - y) + 2y = 9
6 - y + 2y = 9
y = 3 -- (4)
Substituting (4) into (3),
x + 3 = 6
x = 3 -- (5)
According to (4) and (5),
x = 3 , y = 3